The Importance of Strategic, Victim-Centred Human Trafficking Prosecutions - French, Susan; Liou, Cindy C (Anti-Trafficking Review, 2016)
Response to ATR Debate Proposition: ‘Prosecuting trafficking deflects attention from much more important responses and is anyway a waste of time and money’